IDENTIFIKASI PARASIT PADA IKAN NILA (Oreochromis niloticus) DI IRIGASI BARABUNG KECAMATAN DARUSSALAM ACEH BESAR (Identification of Parasites on Nile Tilapia (Oreochromis niloticus) Fish Collected from Barabung Irigation Darussalam Aceh Besar) - Nova Lianda; Yudha Fahrimal; Razali Daud; Rusli Rusli; Dwinna Aliza; Mulyadi Adam (Universitas Syiah Kuala, 2015)
This study was aimed to identify parasite types that infected Nile tilapia (Oreochromis niloticus) fish collected from Barabung irigation Darussalam, Aceh Besar. A total of 26 Nile tilapia fish were collected from Barabung irigation then examined for the presence of ectoparasite and endoparasite at Parasitology Laboratory, Veterinary Medicine Faculty, Syiah Kuala University Banda Aceh. The ectoparasite examination was conducted by observed the external body part of fish macroscopically and microscopically. While endoparasite examination was conducted by observed the inner surface of digestive track. The results showed that four types of parasites were found namely Dactylogyrus sp., Gyrodactylus sp., Camallanus sp., and P. nagpurensis. Overall,73.1% Nile tilapia fish was infested by Dactylogyrus sp., 11.3% was infested by Gyrodactylus , 10 % was infested by Camallanus, and 5% was infested with P. nagpurensis.Key words: endoparasite, ectoparasite, tilapia fish